Molecular dynamics simulation of the brain-isolated single-domain antibody/nanobody from camels through in vivo phage display screening - Hasannejad-Asl, Behnam; Hashemzadeh, Hassan; Pooresmaeil, Farkhondeh; Dabiri, Mehran; Pooresmaeil, Mohammad-Reza; Ahmadvand, Davoud; Hosseini, Arshad (Frontiers in Molecular Biosciences, 2024)
Introduction During the last decade, there has been a significant rise in the use of therapeutic antibodies or passive immunotherapy for treating various conditions like inflammation and cancer. However, these proteins face challenges reaching the brain and often require specialized delivery methods such as single-domain antibodies (sdAbs). Traditional antibodies struggle to efficiently cross the blood-brain barrier (BBB), hindering their effectiveness. Receptor-mediated transcytosis (RMT) offers a promising pathway for transporting large molecules essential for brain function and treatment across the BBB. Methods SdAbs and peptide ligands with an affinity for RMT receptors are commonly employed to enhance the transport of biotherapeutics compounds across the BBB. This research used a sdAbs phage-displayed library from 13 camelus dromedarius samples to identify sdABs that specifically bind to and are internalized by human BBB endothelial cells (ECs) through in vivo panning. Results and discussion One sdAb, defined as FB24, was isolated, sequenced, translated into an open reading frame (ORF), and subjected to three-dimensional (3D) modeling. Molecular docking and molecular dynamics simulations were carried out by the HADDOCK web server and GROMACS, respectively, to evaluate the interaction between FB24 and EC receptors in silico. The docking results revealed that FB24 exhibited binding activity against potential EC receptors with −1.7 to −2.7 ranged z score and maintained a stable structure. The docked complex of FB24-RAGE (receptor for advanced glycation end products, also known as advanced glycation end product receptor [AGER]) showed 18 hydrogen bonds and 213 non-bonded contacts. It was chosen for further analysis by molecular dynamics simulations by GROMACS. This complex showed a stable condition, and its root mean square deviation (RMSD) was 0.218 nm. The results suggest that FB24 could serve as a suitable carrier vector for transporting therapeutic and diagnostic agents across the BBB to the brain through a non-invasive route.